The silhouette zoetrope : a new blend of motion, mirroring, depth, and size illusions - Veras, Christine (2019)
Here, we report a novel combination of visual illusions in one stimulus device, a contemporary innovation of the traditional zoetrope, called Silhouette Zoetrope. In this new device, an animation of moving silhouettes is created by sequential cutouts placed outside a rotating empty cylinder, with slits illuminating the cutouts successively from the back. This “inside-out” zoetrope incurs the following visual effects: the resulting animated figures are perceived (a) horizontally flipped, (b) inside the cylinder, and (c) appear to be of different size than the actual cutout object. Here, we explore the unique combination of illusions in this new device. We demonstrate how the geometry of the device leads to a retinal image consistent with a mirrored and distorted image and binocular disparities consistent with the perception of an object inside the cylinder.